Comparison of Antibacterial Activity of Sambiloto (Andrographis paniculata) Ethanol and Water Stem Extract Against Methicillin-Resistant Staphylococcus aureus (MRSA) ATCC 3351 In Vitro - Ni Wayan Sinta Devi Arini; Bagus Komang Satriyasa; I Made Jawi; Agung Wiwiek Indrayani (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2020)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is penicillin and cephalosporine resistant Staphylococcus aureus which is a major cause of nosocomial infection. Various studies have been conducted for resistant cases, especially herbs which have antibacterial activity. Sambiloto (Andrographis paniculata) is an example of herb which has antibacterial activity due to the presence of andrographolide. Andrographolide soluble in ethanol and poorly in water, while extraction with alcohol causes andrographolide’s degradation. This study aimed to investigate the antimicrobial activity of ethanol and water stem extract and compare them against MRSA ATCC 3351 in vitro.Methods: This is an experimental study with a post-test only control group design and conducted by disc diffusion technique to obtain an inhibition zone against MRSA.Result: The result of this study showed the mean inhibitory zone of ethanol stem extract was 5,87mm, 6,77mm, 7,87mm respectively for 25%, 50%, and 100% concentrations, while 1% concentration did not show antibacterial activity. Water stem extract at 1%, 25%, 50%, and 100% concentrations showed mean inhibitory zone was at 4,57mm, 7,17mm, 8,67mm, and 9,67mm respectively.Conclusion: Ethanol and water stem extract showed antibacterial activity against MRSA. The independent sample t-test didn’t show a difference between ethanol and water stem extract of Andrographis paniculata toward MRSA (p>0,05).